Characteristics and management of very elderly patients with heart failure: a retrospective, population cohort study. (8th October 2022) - Olofsson, Mona; Lindmark, Krister; Stålhammar, Jan; Törnblom, Michael; Lundberg, Anna; Wikström, Gerhard; Boman, Kurt
Abstract: Aims: Unmet needs exist in the diagnosis and treatment of heart failure (HF) in the elderly population. Our aim was to analyse and compare data of diagnostics and management of very elderly patients (aged ≥85 years) compared with younger patients (aged 18–84 years) with HF in Sweden. Methods: Incidence of ≥2 HF diagnosis (ICD‐10) was identified from primary/secondary care in Uppsala and Västerbotten during 2010–2015 via electronic medical records linked to data from national health registers. Analyses investigated the diagnosis, treatment patterns, hospitalizations and outpatient visits, and mortality. Results: Of 8702 patients, 27.7% were ≥85 years old, women (60.2%); most patients (80.7%) had unknown left ventricular ejection fraction; key co‐morbidities comprised anaemia, dementia, and cerebrovascular disease. More very elderly patients received cardiovascular disease (CVD)‐related management after diagnosis in primary care (13.6% vs. 6.5%; P < 0.0001), but fewer patients underwent echocardiography (19.3% vs. 42.9%; P < 0.0001). Within 1 year of diagnosis, very elderly patients were less likely to be hospitalized (all‐cause admissions per patient: 1.9 vs. 2.3; P < 0.0001; CVD‐related admissions per patient: 1.8 vs. 2.1; P = 0.0004) or prescribed an angiotensin‐converting enzyme inhibitor/angiotensin receptor blocker (ACEI/ARB) plus a β‐blocker (45.2% vs. 56.9%; P < 0.0001) or an ACEI/ARB plus a β‐blocker plus a mineralocorticoid receptor antagonist (15.4% vs. 31.7%; P < 0.0001). One‐year mortality was high in patients ≥85 years old, 30.5% (CI: 28.3‐32.7%) out of 1797 patients. Conclusions: Despite the large number of very elderly patients with newly diagnosed HF in Sweden, poor diagnostic work‐up and subsequent treatment highlight the inequality of care in this vulnerable population.